Cultural Context or Generational Cohort: Which Influences Tourist Behavior More? - Pérez-Tapia, Gema; Mercadé-Melé, Pere; Yeong-Hyeon, Hwang; Almeida-García, Fernando (Frontiers in Psychology, 2022)
According to most academics, different generations share common characteristics. This undoubtedly helps to better understand their behavior in different scenarios, predicting their responses. However, this seems questionable and that is the main purpose of this study. This research, although preliminary, aims to question whether generational cohorts define behaviors or whether, on the contrary, it is culture that really constitutes the basis of common behavior, becoming the determining factor of their behavior. To this end, it has been contextualized in a sector that is very sensitive to cultural differences, such as tourism. It will try to confirm if millennials have common characteristics, or if, on the contrary, there are differences between them due to the culture in which they are immersed. Data collection was carried out through a questionnaire administered in 2019 via e-mail to young South Korean and Spanish millennials (born 1982–2002). The results suggest that there do not appear to be common personality traits between the countries analyzed. The differences between the two groups for most personality traits and travel motivations were significant. The findings of this research provide several practical implications since it will make possible a more appropriate management of the tourist destination.